Part III: Minimum Quality Threshold in Preclinical Sepsis Studies (MQTiPSS) for Fluid Resuscitation and Antimicrobial Therapy Endpoints. Issue 1 (January 2019) - Hellman, Judith; Bahrami, Soheyl; Boros, Mihaly; Chaudry, Irshad H.; Fritsch, Gerhard; Gozdzik, Waldemar; Inoue, Shigeaki; Radermacher, Peter; Singer, Mervyn; Osuchowski, Marcin F.; Huber-Lang, Markus
Abstract : ABSTRACT: As outlined in the "International Guidelines for Management of Sepsis and Septic Shock: 2016, " initial fluid resuscitation and administration of antibiotics are key steps in the early management of sepsis and septic shock. However, such clear guidelines do not exist for preclinical sepsis models. To address these shortcomings, the Wiggers-Bernard conference on preclinical sepsis models was held in Vienna in May 2017. The participants reviewed 260 of the most highly cited papers between 2003 and 2012 that used sepsis models. The review demonstrated that over 70% of experiments either did not use or failed to report resuscitation and/or antibiotic treatment. This information served as the basis to create a series of recommendations and considerations for preclinical sepsis models; this Part III report details the recommendations for fluid resuscitation and antibiotic treatment that should be addressed in sepsis models. Similar to human sepsis, fluid resuscitation is recommended in the experimental setting unless part of the study. Iso-osmolar crystalloid solutions are preferred. The administration route and its timing should be adjusted to the specific requirements of the model with preference given to dynamic rather than static hemodynamic monitoring. Predefined endpoints for fluid resuscitation and avoidance of fluid overload should be considered. Preclinical sepsis studies display serious inconsistencies in the use of antimicrobial protocols. To remedy this, antimicrobials are recommended for preclinical studies, with choice and dose adjusted to the specific sepsis model and pathogen (s). Ideally, the administration of antimicrobials should closely mimic clinical practice, taking into account the drug's pharmacokinetic profile, alterations in absorption, distribution and clearance, and host factors such as age, weight, and comorbidities. These recommendations and considerations are proposed as "best practices" for animal models of sepsis that should be implemented.